2018
DOI: 10.1016/j.cognition.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in switching and inhibition predict perspective-taking across the lifespan

Abstract: Studies exploring the influence of executive functions (EF) on perspective-taking have focused on inhibition and working memory in young adults or clinical populations. Less consideration has been given to more complex capacities that also involve switching attention between perspectives, or to changes in EF and concomitant effects on perspective-taking across the lifespan. To address this, we assessed whether individual differences in inhibition and attentional switching in healthy adults (ages 17-84) predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 29 publications
8
77
1
Order By: Relevance
“…Partly supporting our expectations, cognitive flexibility but not working memory showed unique contribution to variance in parental stress. Supporting our results, individual differences in cognitive flexibility have recently been suggested to be important for regulatory capacities associated with perspective taking (Long, Horton, Rohde, & Sorace, ). Previous studies have found that cognitive flexibility is impaired in individuals with SUD (Cunha et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Partly supporting our expectations, cognitive flexibility but not working memory showed unique contribution to variance in parental stress. Supporting our results, individual differences in cognitive flexibility have recently been suggested to be important for regulatory capacities associated with perspective taking (Long, Horton, Rohde, & Sorace, ). Previous studies have found that cognitive flexibility is impaired in individuals with SUD (Cunha et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…As for cognitive abilities, we assessed speakers' verbal and visual working memory (verbal and visual WM) as well as executive control and semantic fluency. As summarised above, verbal WM and executive function have previously been related to verbal recipient design (Hupet et al, 1993;Long et al, 2018;Wardlow, 2013). Furthermore, verbal and visual WM have been found to be related to gesticulation in general (e.g.…”
Section: The Present Studymentioning
confidence: 90%
“…Taking an addressee's perspective into account and designing one's utterances accordingly may be a cognitively demanding process (e.g. Horton & Gerrig, 2005;Horton & Spieler, 2007;Long, Horton, Rohde, & Sorace, 2018;Wardlow, 2013). Considering that healthy human ageing is frequently associated with changes in cognitive functioning (Salthouse, 1991), systematic agerelated changes in multimodal recipient design may be expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to produce coherent speech tends to decline as people grow older. Older adults are more likely to produce tangential, offtopic utterances in conversation (Arbuckle & Gold, 1993;Glosser & Deser, 1992) and to provide irrelevant information when telling a story (Juncos-Rabadan, Pereiro, & Rodriguez, 2005;Marini, Boewe, Caltagirone, & Carlomagno, 2005) or describing an object (Long, Horton, Rohde, & Sorace, 2018). Such changes reduce the effectiveness of communication and the quality of older people's verbal interactions Pushkar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%